(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
Stenochlaena riauensis, a new fern species from Riau, Indonesia is described and illustrated. This species can be distinguished from its most closely related species S. palustris by the position of fertile and sterile pinnae. In the new species, both fertile and sterile pinnae are located on the same frond, the lower part of lamina consisted of sterile pinnae that gradually narrower towards apex forming linear fertile pinnae. Bangladesh J. Plant Taxon. 22(2): 137-141, 2015 (December)